Synthesis and Characterization of Co3O4 and ZnO Nanoparticles Based on Schiff Base Complexes as a Precursor to the Photocatalytic Photodegradation of Congo Red Dye - Raji, Shahad Qasim; Bader, Ali Taleb (Science and Technology Indonesia, 2025)
The synthesis of [Co(HBZAP)(OAC)2]2H2O and [Zn(HBZAP)(OAC)2] H2O complexes was successfully performed through reflux in connection with the Schiff bases synthesized with metal salt acetate hydrate. Identification of the synthesized complexes was performed by Fourier transform infrared FTIR, UV-Vis, magnetic moment,1H, and 13C-NMR spectroscopy and X-Ray diffraction XRD. These studies show the Schiff base ligand as bidentate due to oxygen from the phenolic group and nitrogen from the azomethane group for complexation with Co(II) and Zn(II), resulting in a tetrahedral configuration of the complexes around the metal ions. Conductivity measurements in DMSO demonstrated that none of the complexes would permit the conduction of electricity. Co3O4 and ZnO nanoparticles were synthesized from these Co(II) and Ni(II) complexes. FTIR and UV-Vis spectra, as well as FE-SEM images, were used to identify the synthesized nanostructures. These results show that the Co3O4 and ZnO nanoparticles have cubic and hexagonal systems, respectively. The average crystallite sizes of Co3O4 and ZnO are 36.5 and 31.9 nm, respectively. These nanoparticles show excellent photocatalytic activity when used under UV light to degrade Congo red dye in aqueous media for 120 minutes of 91.4% and 60.6%.